Automatic Segmentation of Lymphatic Perfusion in Patients with Congenital Single Ventricle Defects - Stegmaier, Marietta; Schröder, Christian; Müller, Johanna; Day, Thomas; Cuomo, Michela; Dewald, Oliver; Dittrich, Sven; Kainz, Bernhard (Bildverarbeitung für die Medizin 2024. BVM 2024, 2024)
The Fontan circulation is the surgical end-point for a variety of singleventricle congenital heart lesions. While recent decades have witnessed substantial improvements in survival rates, the associated physiology remains susceptible to severe complications such as protein-losing enteropathy and plastic bronchitis. These complications are often indicative of abnormal congestion in the lymphatic system, underscoring their significance as harbingers of impending comorbidities. An accurate assessment of congestion severity requires the detailed annotation of lymphatic perfusion patterns in each volumetric scan slice. The manual labelling of such intricate data is time-consuming and demands a high level of expertise, rendering it unfeasible within the confines of standard clinical protocols. We use a curated database consisting of manually annotated T2-weighted magnetic resonance imaging (MRI) scans from 71 Fontan patients post-surgery. Following the current state-of-the-art method for biomedical image segmentation, we evaluate its performance on multiple independent test sets regarding the degree of severity and imaging quality. Incorporating the best-performing model,we have developed a user-friendly interface for the automatic segmentation of lymphatic malformations, which will be published before the conference starts.
CRIS-Team Scopus Importer:2024-03-29